Fully guided placement of orthodontic miniscrews- a technical report - Kirnbauer Barbara; Rugani Petra; Santigli Elisabeth; Tepesch Philipp; Ali Kamran; Jakse Norbert (Sciendo, 2019)
Orthodontic miniscrews are used to obtain skeletal anchorage during orthodontic treatment and their application is growing due to the simple method of placement and removal, which invites improved patient compliance without significant impact on function and aesthetics. However, complications and risks are reported that underscore the need for a thorough preoperative assessment to enable accurate placement, especially in confined sites. A novel approach is presented which employs a custom-designed 3D-printed splint to facilitate a fully-guided placement of orthodontic miniscrews.